Features of microcirculation and effectiveness of conservative therapy in exacerbation of chronic tonsillitis - Andrey Y. Ovchinnikov; Evgenii S. Burenkov (Наука и инновации в медицине, 2019)
Objectives to study the characteristics of microcirculation in patients with chronic tonsillitis, caused byStreptococcus pyogenes,with confirmed sensitivity to the group of inhibitor-protected penicillins.